Utilization of Zakat Funds through Distribution of Educational Scholarships (Case Study at Polmed Ziswaf Center) - Zuhratul Husna; Hubbul Wathan; Muhammad Zuhirsyan; Marlya Fatira AK (Proceeding of International Conference on Multidisciplinary Research, 2024)
Education is a very important aspect in making the nation smarter, but there are still educational problems, especially for some students who have financial problems to continue their education. Several universities are trying to alleviate this problem by establishing amil zakat institutions to collect and distribute zakat funds to help students in need. Polmed Ziswaf Center is an institution that manages zakat, infaq, shadaqoh and waqf through campus-based digital programs. The purpose of this research is to provide an overview and evaluation of the performance of the Polmed Ziswaf Center for its success in managing ziswaf funds to empower underprivileged students who have a high desire to learn but have financial limitations at the Medan State Polytechnic through educational scholarships. This research is a type of descriptive qualitative research. The data sources in this research were obtained through observation, interviews and focused discussions at the Polmed Ziswaf Center office. The informant in this research is the distribution and utilization sector on behalf of Dr. Suherman, M.Ag and Collection Division on behalf of M. Yunus, S.Pdi. The data analysis technique in this research uses data triangulation techniques. The results of this research show that the Polmed Ziswaf Center has distributed zakat funds for education through a scholarship program, but it is felt that it is very necessary to develop various other program targets, especially for underprivileged Medan State Polytechnic students.